2013
DOI: 10.1039/c3nr34008b
|View full text |Cite
|
Sign up to set email alerts
|

Co-axial electrospun polystyrene/polyurethane fibres for oil collection from water surface

Abstract: The pollution arising from oil spills is a matter of great concern due to its damaging impacts on the ecological environment, which has created a tremendous need to find more efficient materials for oil spill cleanup. In this work, we reported a sorbent for oil soak-up from a water surface with a high sorption capacity, good selectivity, and excellent reusability based on the hydrophobic-oleophilic fibrous mats that were fabricated via co-axial electrospinning polystyrene (PS) solution as the shell solution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 41 publications
0
87
1
2
Order By: Relevance
“…Lin et al [21] prepared porous polystyrene nanofibers via electrospinning, and they found that the absorbencies of the fibers to motor oil, bean oil, and sunflower seed oil were 113.87, 111.80, and 96.89 g/g, respectively. Additionally, Lin et al [22] also prepared a fibrous membrane consisting of polystyrene and polyurethane fibers via co-axial electrospinning, and their findings showed that the oils amount absorbed by such membrane was about 2-3 times of the oils amount absorbed by conventional polypropylene nonwoven fabrics. Wu et al [23] fabricated porous polystyrene fibers through a facile electrospinning method, and the corresponding electrospun resultant exhibited outstanding oils absorption performance.…”
Section: Introductionmentioning
confidence: 96%
“…Lin et al [21] prepared porous polystyrene nanofibers via electrospinning, and they found that the absorbencies of the fibers to motor oil, bean oil, and sunflower seed oil were 113.87, 111.80, and 96.89 g/g, respectively. Additionally, Lin et al [22] also prepared a fibrous membrane consisting of polystyrene and polyurethane fibers via co-axial electrospinning, and their findings showed that the oils amount absorbed by such membrane was about 2-3 times of the oils amount absorbed by conventional polypropylene nonwoven fabrics. Wu et al [23] fabricated porous polystyrene fibers through a facile electrospinning method, and the corresponding electrospun resultant exhibited outstanding oils absorption performance.…”
Section: Introductionmentioning
confidence: 96%
“…Due to the good elastic and mechanical properties, electrospun PU membranes have practical application in oil/water separation. [52][53][54] Wang and Yang et al…”
Section: Electrospinning Methodsmentioning
confidence: 99%
“…This is the¯rst report to demonstrate a self-healing membrane for oil/water separation, which provides the fundamental research for the development of advanced materials for oil/water separation. Lin et al 54 reported that hydrophobic-oleophilic¯brous mats were fabricated via co-axial electrospinning polystyrene (PS) as the shell solution and polyurethane as the core solution. The¯ne structures of as-prepared¯bers were regulated by manipulating the spinning voltages, the concentration of the core, and solvent compositions in shell solutions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The nanofibrous materials obtained by electrospinning has nonwoven structure with unique features, including interconnected pores and a very large surface to volume ratio, which enable such nanofiber materials to have many applications such as filters, energy storage, environment engineering, protective clothing and tissue engineering [4,5]. With the rapid increase in application of nanofibers in more and more industry areas, electrospinning has been one of the most important and basic techniques in the fabrication of nanofibers since the early 2000s.…”
Section: Introductionmentioning
confidence: 99%